Child-Centrism as an Adaptive Parenting Style: A Prospective Study in Motherhood from Women’s Life Satisfaction Including Cognitive–Emotional Resources - Celia Arribas; Patricia Catalá; Cecilia Peñacoba; Maria Crespo; Miri Kestler-Peleg (Children)
Background: Child-centrism refers to a parenting style where parents prioritize children’s needs above their own. Early research suggested that it could harm parental well-being, yet recent findings indicate that mothers adopting this style may experience greater psychological well-being and meaning in child-rearing. This study examines child-centrism as a complex, context-dependent style and aims to clarify its adaptive or non-adaptive nature through a prospective, longitudinal approach. Methods: A four-wave design included 231 mothers assessed at (T1) third trimester of pregnancy, (T2) eight weeks postpartum, (T3) five months postpartum, and (T4) five years postpartum. Self-reported measures included life satisfaction (T1), maternal self-efficacy (T2), positive affect (T3), and child-centrism (T4). Sociodemographic data (age, family status, education, income, working) were also collected. Statistical analyses tested a serial mediation model. Results: Life satisfaction at T1 significantly predicted maternal self-efficacy at T2 (p = 0.002), which in turn enhanced positive affect at T3 (p < 0.001). Positive affect at T3 then positively influenced child-centrism at T4 (p = 0.023). However, life satisfaction did not directly affect child-centrism (p = 0.970), indicating a sequential mediation pathway rather than a direct link. Conclusions: These findings highlight that higher prenatal life satisfaction indirectly fosters an adaptive form of child-centrism through maternal self-efficacy and positive affect. Integrating motherhood into a woman’s sense of identity appears to be a protective factor, promoting healthier cognitive and affective parenting resources. Preventive interventions could focus on strengthening women’s life satisfaction and self-efficacy early in pregnancy, thereby enhancing affective well-being and potentially leading to a more meaningful, child-centric parenting style. Further research should include broader maternal and child well-being indicators.